26 ASSOCIATION BETWEEN DIAGNOSIS OF HYPERTENSION AND HYPERTENSIVE RESPONSE DURING TREADMILL IN ARMY PERSONNEL UNDERGOING MEDICAL CHECK-UP, HOW INFLUENTIAL IS IT?. (July 2018) - Pranata, Raymond; Yonas, Emir; Chintya, Veresa; Pamungkas, Bambang; Pratama, Vireza; Permana, Bayu Arif; Syahlul, Dina Evalina; Harsoyo, Agus
Abstract: Introduction: Hypertensive response to exercise (HRE) is defined as a peak systolic blood pressure >210 mmHg in Men and >190 in women or difference between peak and baseline SBP for at least 60 mmHg in men and 50 mmHg in women during exercise testing. Non-hypertensive individuals with exaggerated blood pressure responses during exercise stress testing are more likely to develop hypertension. A HRE is not associated with increased mortality when baseline blood pressure is taken into account. However, a HRE during submaximal exercise may be associated with an increased risk for cardiovascular death in non-hypertensive individuals. [1, 2, 3] Objectives: Our aim is to know the magnitude of difference in HRE during treadmill exercise between subjects with a history of hypertension and those without and factors affecting or affected by it. Methods: This was a cross-sectional observational study. Their subjects were 326 consecutive army personnel who were referred to cardiology and vascular department for further cardiovascular examination from medical check-up unit in Central Army Hospital Gatot Soebroto. 59 subjects were excluded because treadmill test was not ordered. Out of 267 subjects, 102 were hypertensive and 165 were not hypertensive. Results: Hypertensive response to exercise was more frequently found in those with a history of hypertension (OR 1.924, 95% CI 1.17–3.28, p = 0.013). There was a decreasing trend in HRE with higher physical activity (p = 0.009). Presence of LVH is more common in those with HRE (OR 1.835, 95% CI 1.033–3.261, p = 0.037). There was no significant difference between those with or without HRE and presence of diseased vessel. There was also no difference in prevalence of one VD, two VD and three VD. We analysed subjects with HRE, there was 47.4% with history of hypertension and 50.5% without. There was no association between LVH and presence of traditional risk factors, physical activity and impaired renal function in subjects with in these subjects. Conclusion: Hypertensive response to exercise during treadmill exercise test was significantly higher in patients with a history of hypertension and tends to lower with increasing physical activity. Left ventricular hypertrophy was also more frequently found in these subjects.